Analysis of Implementation of Mayor Regulation Number 31 of 2018 on BMD Removal Procedure in Surakarta - Intan Septiana Utami; Hananto, Santoso Tri; Jannah, Miftahul (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
The Standard Operating Procedure for BMD elimination becomes the realization of BPKAD Surakarta in attempting to manage BMD. This study set out to investigate the implementation of the BMD removal process in Surakarta and to prove the suitability of Mayor Regulation No. 31 of 2018 with the BMD removal procedure in Surakarta. The present study employs descriptive analysis including data collection, literature study, observation, and interviews. The results of this study indicate that the SOP for eliminating BMD at BPKAD Surakarta is following Mayor Regulation No. 31 of 2018. Even though the applicable guidelines are appropriate, the implementation of the BMD removal process is inseparable from several obstacles, such as there are still differences in objects between the physical BMD in the field and the list, plans to write off goods, and human resources less competent in the field of eliminating BMD. There are no guidelines for naming goods and lack of human resources in OPD in the BMD as well as the sorting process has not been recorded at SIMDA. The researchers suggest that separating between BMD that has been recorded at SIMDA, holding refreshments, coordinating meetings on SOP that apply within a certain period or whenever there is a renewal of regulations, making preparation of standards for naming goods, and collaborating with third parties in the form of professional service providers to sort BMD recorded in SIMDA.